Accuracy of vertical datum surfaces in coastal and offshore zones. Issue 331 (1st July 2013) - Iliffe, J C; Ziebart, M K; Turner, J F; Talbot, A J; Lessnoff, A P
<x xml:space="preserve">Abstract</x> The Vertical Offshore Reference Frames (VORF) project is described, with a summary of the methodology and an explanation of the data sets used. The latter include satellite altimetry, tidal and geoid models, long and short term tide gauge data, and specially undertaken GNSS observations. This paper goes on to describe the theoretical basis for deriving spatially variant error estimates that respond to the varying quality of the input data. The paper then describes the testing programme undertaken by the United Kingdom Hydrographic Office, which has included 245 checks on datum connections at mostly coastal points, 63 comparisons between VORF-corrected tidal levels observed with GNSS and tide gauge data, and six specially commissioned offshore tide gauge deployments. It is shown that across the vast majority of the domain of applicability the VORF surfaces meet their target accuracies of 0·10 m inshore and 0·15 m offshore (both 1σ values) and the formal uncertainties are a fair reflection of the errors actually encountered. The main discrepancy between the modelled surfaces and the test data is found in the sharply varying tidal regime south of Portland on the south coast of England; however, preliminary results from incorporating the next generation of global ocean tide models show a marked improvement in this area.